Estimation of results of diversification of trade flows in the enterprise - Коваленко, Катерина Сергіївна (Technology audit and production reserves, 2013)
The paper considers the main components of the results, which the enterprise obtains introducing the strategy of diversification of trade flows into its activity. The purpose of the study is the formation and evaluation of the results of introduction of trade flow diversification in the enterprise. During the study, the methods of theoretical generalization, systematization and comparative analysis were applied, which allowed to determine and formulate the essence of such categories as "diversification of trade flows", "result". The methods of determining the results, with the use of which they can be assessed are presented in the paper. The proposed analysis allows to estimate both financial and non-financial results, which the enterprise obtains at the diversification of trade flows and to determine the efficiency and feasibility of such introduction. The research results can be used by the head of the enterprise for the evaluation of the efficiency of trade flow diversification and ensuring of stable operation of the enterprise. It is possible to make amendments and additions to the proposed methods of result evaluation, depending on the specifics of the enterprise activity. However, the main component of the analysis of results of trade flow diversification is the change of enterprise profits.